Powiązania sieciowe w funkcjonowaniu małych i średnich przedsiębiorstw w Polsce i Unii Europejskiej - Bucka, Maria (The Web Connections in Small Enterprises Activity in Poland and in the European Union, 2008)
Poland's entry into the European Union led to the confrontation of Polish small and medium-sized businesses with the tough forcing competion, both locally and abroad. Operating single-handed lias proved increasingly difficult; therefore such businesses have started looking for various tools that would enhance their competitiveness and economic stability. One of these tools may consist in establishing networks and clusters of small and medium-sized companies. The goal of this paper is to clarify the cluster issue and indicate the benefits of establishing such clusters for small and medium-sized companies in Poland.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 270-281